The utility of Fine Needle Aspiration Cytology (FNAC) in the diagnosis of head and neck lesions at tertiary health care level - Dr. Dipti Rameshbhai Patel; Dr. Shiv Nandan Chawla (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: FNAC is particularly suitable in the head and neck areas due to its easy accessibility of target sites, minimally invasive nature, excellent patient compliance, and helping of avoidance of surgery in conditions like non-neoplastic, inflammatory, and some tumors. Aim: To assess the prevalence of different types of head and neck lesions and to test the utility of Fine Needle Aspiration Cytology (FNAC) in the diagnosis of head and neck lesions. Material and Methods: A retrospective study of 224 FNAC of head and neck swellings performed as an outdoor procedure from Jan 2018 to June 2019 at the American International Institute of Medical Sciences (AIIMS), GBH General and cancer hospital, Udaipur, Rajasthan. Results: Out of 224 cases, major aspirates were from lymph node 123 (54.91%), followed by skin and soft tissue 42 (18.75%), thyroid 40 (17.85%), salivary gland 13 (5.80%), and Oral cavity 06 (2.67%). Malignant lesions were higher in lymph node 69 (56.09%) and in oral cavity 05 (83.33%). Metastatic carcinoma 66 (53.65%) and lymphoma 03 (2.43%). Colloid goiter 24 (60%), keratinous cyst 27 (64.28%), and Pleomorphic adenoma 04 (30.76%) were common benign lesions in the thyroid, skin and soft tissue, and salivary gland respectively. Conclusions: FNAC can be effectively used in the diagnosis and planning management of various head and neck swellings because it is safe, relatively painless, rapid, outdoor procedure and can differentiate benign from malignant lesions and gives clues for occult primaries in metastatic malignancy.